Publishing for tenure and beyond - Silverman, Franklin H. (Westport Praeger, 1999)
Silverman provides graduate students who intend to pursue a career in academia and tenure-track junior faculty with candid information about developing an adequate publication record. The book also provides graduate students, tenured faculty, and others with information they need to maximize the likelihood of having their articles accepted for publication by peer-reviewed professional, scientific, and scholarly journals. The focus throughout is on how editorial boards and tenure committees tend to function rather than on how they are supposed to function. Anyone dealing with academic publishing will find this book an indispensable resource. Topics dealt with include coping with the fear of writing for publication, options for scholarly publishing, identifying "ideal" publishing-for-tenure projects, understanding and coping successfully with peer review process, finding the time to write scholarly publications, and standards for writing and organizing scholarly articles for print and electronic journals. It also covers securing permission to include copyrighted material in your work that does not fall under the doctrine of fair use, submission strategies for getting articles published in academically-respectable journals, and "gray area" plagiarism and other breaches of academic ethics. It shows how to prepare the publication section of a promotion and tenure application. It offers advice on finding funding for beginning scholars and publishing options for surviving post-tenure reviews. Lastly, the book gives practical advice on coping with manuscript rejection.